Sleep Quality in Undergraduate Medical Students of Birat Medical College Teaching Hospital (Birat Journal of Health Sciences, 2025)
Introduction: Inadequate sleep could lead to poor performance of work or studies. Medical students can have inadequate sleep due to overloaded medical curriculum and can lead to poor performance in academics.Objectives:  The objective was to know the sleep quality of medical students of Birat Medical College Teaching Hospital.Methodology: A cross sectional study was conducted from October 1, 2020 to December 30, 2020 among 131 medical students of Birat Medical College Teaching Hospital. Ethical clearance was taken from the Institutional Review Committee (IRC) of Birat Medical College Teaching Hospital. Informed consent was taken from individual students. A pretested self-administered questionnaire using Pittsburgh Sleep Quality Index was given to study participants. The collected data was entered in Microsoft Excel 2016 and analyzed by SPSS version 25.Results: The prevalence of poor sleep quality among medical students, as indicated by a Global PSQI score greater than 5, was 81 (61.8%), with 42 (60%) of male students and 39 (63.9%) of female students. The mean sleep duration across all participants was 6.7 ± 1.2 hours, indicating that most students were not meeting the recommended sleep duration.Conclusion: A significant proportion of medical students reported poor sleep quality, with female students and first-year students being more affected. The majority of students experienced sleep deprivation, with most sleeping less than the recommended 8 hours per night, and only a small fraction meeting the ideal sleep duration.